Remarkable reprodutive spurting behaviour of endangered thick shelled river mussel, Unio crassus - Aldridge, David C. (2018)
Freshwater mussels (Unionida) dominate the biomass and are important keystone organisms in many rivers, yet they are declining precipitously worldwide. Their dispersal is facilitated by possession of parasitic larvae (glochidia) which typically encyst and metamorphose on the gills and fins of host fishes. Long eo-evolutionary histories in some North American mussels has resulted in specificity towards single host fish species that share the same microhabitat as the mussel and has led to the development of lures and behaviours that dramatically increase the likelihood of attachment and successful transmission. Elsewhere in the world, mussels are typically more generalist in host use and thought to release glochidia freely into the water column without using specific lures and attractants. Here we show that the endangered European thick shelled river mussel, Unio crassus, displays a remarkable spurting behaviour where females migrate to river margins and project jets of water up to 1m back into the channel. Spurted material carries glochidia and attracts larval host fishes thus increasing the likelihood of successful transmission. Mature glochidia remain viable for up to 48 hours and carry long larval threads, which can wrap around fixed and floating debris thus keeping the glochidia within the water column. This unique spurting behaviour may explain the disappearance of U. crassus from regulated rivers, where margins have been lost through impoundment, or where increased sporadic discharges displace gravid females from shallow water. The reproductive behaviour of many endangered freshwater mussels is largely unknown but may be central to explaining the dramatic decline in these important ecosystem engineers.